Tempting All the Gods Joseph P. Kennedy, Ambassador to Great Britain, 1938-1940 - Vieth, Jane Karoline (Book collections on Project MUSE., 2021)
" 'Tempting All The Gods' is a detailed study of Joseph P. Kennedy's diplomatic career in London. It examines Kennedy's role as ambassador from 1938 to 1940. It describes his attitudes toward American foreign policy before the outbreak of war and after the war began, explains why he held those views, and assesses their impact on Anglo-American relations"--